2013
DOI: 10.1002/jgrd.50308
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic structure of a wildland fire plume observed by Doppler lidar

Abstract: [1] Wildland fires present a challenging environment to make meteorological measurements. Observations in the vicinity of wildland fires are needed to better understand fire-atmosphere interactions and to provide data for the evaluation of coupled fire-atmosphere models. An observational study was conducted during a low-intensity prescribed fire in an area of complex terrain with grass fuels east of San José, California. A ground-based scanning Doppler lidar acquired radial wind velocities and backscatter inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…The edge detection al- gorithm uses a combination of the lidar signal-to-noise ratio (SNR) and attenuated backscatter coefficient to isolate the plume. Similar approaches are presented in previous studies (Kovalelv et al, 2005;Charland and Clements, 2013). In our analysis, we first apply a 5th order Butterworth filter with a 5-point window to the SNR data along each lidar beam to eliminate some of the instrument noise.…”
Section: Plume Edge Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The edge detection al- gorithm uses a combination of the lidar signal-to-noise ratio (SNR) and attenuated backscatter coefficient to isolate the plume. Similar approaches are presented in previous studies (Kovalelv et al, 2005;Charland and Clements, 2013). In our analysis, we first apply a 5th order Butterworth filter with a 5-point window to the SNR data along each lidar beam to eliminate some of the instrument noise.…”
Section: Plume Edge Detectionmentioning
confidence: 99%
“…Due to these sensitivities numerous previous studies have used lidars to examine smoke layers and smoke plumes (Banta et al, 1992;Kovalev et al, 2005;Pahlow et al, 2005;Charland and Clements, 2013;Lareau and Clements, 2015).…”
Section: Lidar Sensitivitymentioning
confidence: 99%
“…Lidar observations indirectly provide a measure of smoke density distribution. The usefulness of ground-based scanning lidars to assess plume rise dynamics and height was illustrated recently by Kovalev et al (2009), Wold et al (2010 and Charland and Clements (2013). Utkin et al (2003), Lavrov et al (2006) and Fernandes et al (2006) demonstrated the feasibility of forest-fire smoke detection using lidar even if the source is out of sight or under unfavourable visibility conditions.…”
Section: Leroy-cancellieri Et Al: Evaluation Of Wildland Fire Smomentioning
confidence: 95%
“…Key meteorological variables to characterize fire weather conditions and surface meteorology will include ambient air temperature, humidity, near-surface wind speed and direction of ambient and fire-induce wind fields [39]. Plume rise, entrainment, and fire-atmospheric circulations associated with the plume will be measured using in situ towers (e.g., [40]) and ground-based scanning Doppler LiDAR systems (ground and/or aircraft) [40][41][42], and a scanning Doppler dual-polarized, Ka-band radar system. Radars with dual-polarization capability have been shown to be useful for observing smoke plume structures and plume microphysics [43].…”
Section: Plume Dynamics and Meteorologymentioning
confidence: 99%